The component structure of job satisfaction of medical workers with different working conditions - Veldbrekht, Olena Oleksandrivna; Bovdyr, Olena Serhiivna; Samkova, Olesia Мykolayivna (Insight: the psychological dimensions of society, 2021)
Nowadays, the profession is regarded as an important part of a person, which should promote his/her self-development, meet some social and existential needs. The purpose of the article is to cover the diagnostic scope of the job satisfaction questionary (JSQ) in individual counseling and monitoring of organizational space. Methods: it is presented an original tool with proven validity and reliability consisting of 38 items – job components (process, conditions of implementation, results) which render individual needs in professional activity. It allows assessing the five components of satisfaction: the resourcefulness of working space, work organization, work & life balance, the social value of work, the space of professional self-realization. Qualitative analysis of individual items demonstrates fundamental motivators, frustrated needs, and “pain points” of employees. The research has analyzed diagnostic results of 104 representatives of medical professions who have 3-35 years of experience: 55 paramedics and emergency doctors, 26 employees of a private clinic, 23 volunteers. Results of the comparative analysis of groups show that, depending on working conditions, representatives of different teams are characterized by unlike components of job satisfaction. This uniqueness is the key to developing programs for social and psychological support of employees, training activities, and organizational interventions. Group satisfaction profiles make it possible to assess the individual results of some team members objectively. This is the background against which the subjective perception of professional life unfolds; common factors can mitigate or exacerbate existing problems. Common features of the sample comprise dissatisfaction with tangible and intangible remuneration for work, awareness of the social usefulness of work, continuous training. Conclusions emphasize that different professional groups are distinguished by challenging aspects of work and their intensity. Regular monitoring of teams using the job satisfaction questionnaire makes it possible to timely respond to the relevant challenges ensuring the psychological well-being of professionals.